EVALUATION USE OF BACILLUS MUCILAGINOSUS AS BIOFERTILIZER INTERFERE WITH GLOMUS MOSSEAE ON GROWTH AND YIELD OF CORN - & et al., Hussien (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The current study was aimed to isolate and diagnosis Bacillus mucilaginosus and evaluate its use as biofertilizer alone or interfere with Glomus mosseae on growth and yield of corn (Zea mays L.) Randomized completely block design was used at the Field of College of Agriculture- University of Baghdad Al-Jadriya in silt clay loam soil. The biofertilizer was used alone or as combination that added with or without 50 Kg P ha¹ of rock phosphate and with or without 120 Kg K ha¹ while, 250 Kg N ha¹ was added as urea (46%N) to all treatments. Results showed the superiority of bacterial or fungal biofertilizer on enhancing all growth traits of corn and the addition of B . mucilaginosus together with Glomus mosseae resulted superiority for plant height , dry weight of vegetative part , grain yield and biological yield with the values 229.4 cm , 180.7 gm .plant¹,12.17 tons ha¹ and 19.59 tons ha¹ respectively. As well as treatment gave significant increase equal the increase in the yield due to addition of completely recommended mineral fertilizer which was 12.14 tons ha-1 .